ANALYSIS OF RICE FARMING PERFORMANCE BASED ON VARIETIES IN RAINFED RICE FIELDS IN BATANG KUIS - Ni’mal Hamdi; Nurliana Pulungan; Irshad Ahmad Reshi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study aims to evaluate the performance of rice farming based on differences in varieties used, namely national superior varieties, local superior varieties, and hybrids in rainfed rice fields. The research method used was a survey of rice farmers with a quantitative descriptive approach. The results showed that the highest productivity was obtained by the Super Bernas hybrid variety with an average production of 7,454 kg/ha/planting season, followed by the local variety Anak Daro at 6,746 kg/ha, and the national variety IR 42 at 6,417 kg/ha. The highest production costs were also found in the Super Bernas variety, but were offset by the highest net income of Rp6,809,118/ha. In terms of efficiency, the Super Bernas variety showed the highest RCR value of 1.36, which means it is more efficient than other varieties. Overall, hybrid varieties provide higher production results and income despite requiring higher production costs.